Marketing Strategy Development of Processed Seafood Souvenir During the Covid-19 Pandemic at IKM “Bahek Ewaki”, Central Bangka Regency - Eni Karsiningsih; Anisa Anisa; Rufti Puji Astuti (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2023)
Marketing strategy development is one of the important elements that must be possessed by every Small and Medium Industry (IKM). The Covid-19 pandemic has caused the income of IKM "Bahek Ewaki" to decrease. This study aims to determine the difference in profits before and during the Covid-19 pandemic and analyze the marketing strategy during the Covid-19 pandemic. The research method used is a case study. Differences in profits before and during the Covid-19 pandemic were analyzed by Wilcoxon analysis. The marketing strategy for processed seafood souvenirs was analyzed using SWOT and followed by QSPM analysis. The results of the study show that business profits before and during the Covid-19 pandemic were significantly different, namely, a decrease of 37%. The results of the SWOT analysis recommend that IKM "Bahek Ewaki" carry out a growth oriented strategy. The priority strategies based on the QSPM matrix are: (1) providing affordable prices and increasing promotions with the highest TAS score of 7.54; (2) maintain and improve the quality of products and services with a TAS score of 7.51; (3) maintaining cooperation with suppliers or competitors with a score of 7.5; (4) maximize strategic location and facilities with a score of 7.48. During the Covid-19 pandemic, IKM "Bahek Ewaki" should increase sales volume online through online media.